CONCEPÇÕES E PRÁTICAS DE MÚSICA NA ESCOLA NA VISÃO DE ALUNOS DE 8ª SÉRIE DO ENSINO FUNDAMENTAL: AS CONTRADIÇÕES ENTRE O LEGAL E O REAL - Sebben, Egon Eduardo (2009)
This work has as its objective to investigate the musical conceptions and practices of students from the 8th grade of the elementary education and the policies concerning the art and music education at school in Ponta Grossa – Paraná, having as analysis vectors the media and the school musical practices. The proposed specific objectives are: to investigate the musical taste and practices of students from the 8th grade of the elementary education; to analyze the educational policies for the art and music education and the musical practices of the school, in order to verify in what level they meet the musical taste demand and the musical experience of the students; to investigate the students conceptions concerning the art and music education at school. The proposal of the research undertaking set off from the disquiet about the relation of the students with music, their practices and musical consumption, keeping in sight the Law Project 330/06, approved as an ordinary Law n.11769/2008, which makes obligatory the music education at school. The method applied is based in the dialectical and historic materialism, considering that the subjects and the research spaces are inserted into a wider economical, political and social reality. The prioritized instrument of research was the questionnaire, applied in 297 students from the 8th grade from 13 state public schools and 6 private schools from Ponta Grossa - Paraná. The obtained results indicate that the investigated adolescents have musical knowledge, showing themselves as active music consumers, and their taste derivates from the mediatical emissions, mostly based on the internet. However, the school does not incorporate this knowledge, reducing not only the music, but also the art to a secondary situation in the school environment. The educational policies are configured as an important way of democratization to the artistic languages access, but they need to be readjusted and rethought according to the contexts in which they are inserted. The verification that the school does not work the musical and artistic knowledge properly, and does not consider important adolescents practices knowledge, leads to reflect about the imposed challenges by the new law which institutes the obligation of music in the basic education.